Maternal feeding practices and children's eating behaviours: A comparison of mothers with healthy weight versus overweight/obesity. (1st September 2017) - Haycraft, Emma; Karasouli, Eleni; Meyer, Caroline
Abstract: This study aimed to explore differences between mothers with healthy weight versus overweight/obesity in a wide range of their reported child feeding practices and their reports of their children's eating behaviours. Mothers (N = 437) with a 2-6-year-old child participated. They comprised two groups, based on their BMI: healthy weight (BMI of 18.0–24.9, inclusive) or overweight/obese (BMI of 25.0 or more). All mothers provided demographic information and completed self-report measures of their child feeding practices and their child's eating behaviour. In comparison to mothers with healthy weight, mothers with overweight/obesity reported giving their child more control around eating (p < 0.001), but encouraged less balance and variety around food (p = 0.029). They also had a less healthy home food environment (p = 0.021) and demonstrated less modelling of healthy eating in front of their children (p < 0.001). There were no significant differences in mothers' use of controlling feeding practices, such as pressure to eat or restriction, based on their own weight status. Mothers with overweight/obesity reported their children to have a greater desire for drinks (p = 0.003), be more responsive to satiety (p = 0.007), and be slower eaters (p = 0.034). Mothers with overweight/obesity appear to engage in generally less healthy feeding practices with their children than mothers with healthy weight, and mothers with overweight/obesity perceive their children as more avoidant about food but not drinks. Such findings are likely to inform future intervention developments and help health workers and clinicians to better support mothers with overweight/obesity with implementing healthful feeding practices and promoting healthy eating habits in their children.